2009
DOI: 10.1088/0953-4075/42/18/185006
|View full text |Cite
|
Sign up to set email alerts
|

Spectral distribution of atomic fluorescence coupled into an optical nanofibre

Abstract: We analyse the lineshape of the fluorescence emitted by a cloud of optically excited cold atoms and coupled into an optical nanofibre. We examine the efficiency of the fluorescence coupling and describe the asymmetry of the lineshape caused by the redshifts arising from both the van der Waals and Casimir–Polder interaction of the atoms with the surface of the optical nanofibre. We compare the contributions of the van der Waals and Casimir–Polder redshifts and show that the lineshape of the fluorescence coupled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 37 publications
(72 reference statements)
0
43
1
Order By: Relevance
“…The interaction of atoms with a dielectric nanofiber has been studied theoretically in a number of papers Le Kien et al (2005bKien et al ( , 2006; Klimov and Ducloy (2004);Russell et al (2009); Minogin and Nic Chormaic (2010); Frawley et al (2012a). They demonstrate that the nanofiber modifies the boundary conditions and density of modes, affecting decay properties of the atom.…”
Section: Atom-surface Interactionsmentioning
confidence: 99%
“…The interaction of atoms with a dielectric nanofiber has been studied theoretically in a number of papers Le Kien et al (2005bKien et al ( , 2006; Klimov and Ducloy (2004);Russell et al (2009); Minogin and Nic Chormaic (2010); Frawley et al (2012a). They demonstrate that the nanofiber modifies the boundary conditions and density of modes, affecting decay properties of the atom.…”
Section: Atom-surface Interactionsmentioning
confidence: 99%
“…Van der Waals interactions were manifested in the frequencydependent fluorescence power coupled from atom cloud into TNF. These interactions lead to a pronounced asymmetry in the lineshape of the coupled fluorescence spectrum 32 . It was observed that this asymmetry increased when the atom cloud around TNF was more compact and also when the radius of TNF was increased 32 .…”
Section: Fluorescence Detectionmentioning
confidence: 99%
“…These interactions lead to a pronounced asymmetry in the lineshape of the coupled fluorescence spectrum 32 . It was observed that this asymmetry increased when the atom cloud around TNF was more compact and also when the radius of TNF was increased 32 . Asymmetry occurs due to bound-bound transitions of the ground and excited state van der Waals potentials.…”
Section: Fluorescence Detectionmentioning
confidence: 99%
“…The ground-state cesium atom has its dominant (D 2 ) line at 852 nm, which gives a van der Waals constant of C 3 = 2π × 1.56 kHz μm 3 [23], and this value will be used throughout this paper. In the following we will also use the simplified expression (14) whenever justified while making sure the full expression gives identical results.…”
Section: Van Der Waals Interactionmentioning
confidence: 99%